Airway Management of the Deformed Trachea Using T-Tube Stents in Patients with Mucopolysaccharidosis Type IVA. (May 2022) - Lee, Yi-Hao; Hsieh, Li-Chun; Su, Chin-Hui; Lin, Hsiang-Yu; Lin, Shuan-Pei; Lee, Kuo-Sheng
Introduction: Mucopolysaccharidosis (MPS) type IVA usually results in airway obstruction due to thoracic cage deformity and crowding of intrathoracic structures, causing tracheal compression by the tortuous innominate artery. Objectives: To offer an alternative and effective method in dealing with the challenged deformity of the airway in patients with MPS type IVA. Methods: We present 3 patients with MPS type IVA who underwent airway stenting using Montgomery ® T-tube stents. Three-dimensional reconstructed computed tomography was essential to design the T-tube and evaluate the anatomical relationship between the innominate artery and the trachea. The Y-shaped Montgomery ® Pediatric Safe-T-Tube™ is more suitable for MPS type IVA. Regular follow-ups using fiberoptic bronchoscopy are necessary to evaluate the complications. Results: All 3 patients had good outcomes during the follow-ups until present, despite the complication of granulation formation, which was resolved by revising the limbs of the T-tube. Conclusions: T-tube stents placed below the vocal cord may restore airway patency and preserve laryngeal function, including respiration, phonation, and swallowing, in patients with MPS type IVA.